Implementasi Analytical CRM pada Sistem Informasi Rekam Medis Rehabilitasi Pasien Penyalahgunaan Narkoba (Studi Kasus: Yayasan Cipta Wening Kuningan) - xabar Al Hasim (NUANSA INFORMATIKA, 2017)
Implementation of Analytical (Customer Relationship Management) CRM on Medical Record Information System Rehabilitation of Drug Abuse Patient is a form of information technology strategy that can help perform data management of rehabilitation medical record, while its development model use Analytical CRM model. Analytical CRM is one part of the CRM method that involves customers directly and analyzes the customer's needs to make it easier and more efficient in terms of information delivery so that customers are more comfortable and trust to channel their patients. The design system used with waterfall method, the tool used to design the system in the form of flowmap, context diagram, DFD (Data Flow Diagram), ERD (Entity Relationship Digram) and table relation, while data collection techniques using research methods by way of observation, interview and literature study. This application is built using PHP and MySQL programming languages. With this system is expected to facilitate the Foundation Cipta Wening Kuningan in managing patient medical record data